Improving patient-centeredness of fertility care using a multifaceted approach: study protocol for a randomized controlled trial - Huppelschoten, Aleida G (BioMed Central, 2012)
BACKGROUND: Beside traditional outcomes of safety and (cost-)effectiveness, the Institute of Medicine states patient-centeredness as an independent outcome indicator to evaluate the quality of healthcare. Providing patient-centered care is important because patients want to be heard for their ideas and concerns. Healthcare areas associated with high emotions and intensive treatment periods could especially benefit from patient-centered care. How care can become optimally improved in patient-centeredness is unknown. Therefore, we will conduct a study in the context of Dutch fertility care to determine the effects of a multifaceted approach on patient-centeredness, patients’ quality of life (QoL) and levels of distress. Our aims are to investigate the effectiveness of a multifaceted approach and to identify determinants of a change in the level of patient-centeredness, patients’ QoL and distress levels. This paper presents the study protocol. METHODS/DESIGN: In a cluster-randomized trial in 32 Dutch fertility clinics the effects of a multifaceted approach will be determined on the level of patient-centeredness (Patient-centredness Questionnaire – Infertility), patients’ QoL (FertiQoL) and levels of distress (SCREENIVF). The multifaceted approach includes audit and feedback, educational outreach visits and patient-mediated interventions. Potential determinants of a change in patient-centeredness, patients’ QoL and levels of distress will be collected by an addendum to the patients’ questionnaire and a professionals’ questionnaire. The latter includes the Organizational Culture Assessment Instrument about the clinic’s culture as a possible determinant of an increase in patient-centered care. DISCUSSION: The study is expected to yield important new evidence about the effects of a multifaceted approach on levels of patient-centeredness, patients’ QoL and distress in fertility care. Furthermore, determinants associated with a change in these outcome measures will be studied. With knowledge of these results, patient-centered care and thus the quality of healthcare can be improved. Moreover, the results of this study could be useful for similar initiatives to improve the quality of care delivery. The results of this project are expected at the end of 2013. TRIAL REGISTRATION: Clinicialtrials.gov NCT01481064